pharmaceutical-sciences 2020
DOI: 10.36468/pharmaceutical-sciences.650
|View full text |Cite
|
Sign up to set email alerts
|

Targeting NM23-H1-mediated Inhibition of Tumour Metastasis in Viral Hepatitis with Bioactive Compounds from Ganoderma lucidum: A Computational Study

Abstract: This is an open access article distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 3.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as the author is credited and the new creations are licensed under the identical terms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 9 publications
0
67
0
Order By: Relevance
“…Target identification is an important component for the development of therapeutic and diagnostic markers for metabolic, infectious [20][21][22][23][24][25], autoimmune [26,27,28] and systemic disorders. Computational tools have long been used for the purpose of rapid identification of these potential targets from several sources [29][30]. Dental caries being a serious illness in children has to be identified at the right time and treated using drugs that do not give rise to resistant forms [31][32][33][34].…”
Section: Resultsmentioning
confidence: 99%
“…Target identification is an important component for the development of therapeutic and diagnostic markers for metabolic, infectious [20][21][22][23][24][25], autoimmune [26,27,28] and systemic disorders. Computational tools have long been used for the purpose of rapid identification of these potential targets from several sources [29][30]. Dental caries being a serious illness in children has to be identified at the right time and treated using drugs that do not give rise to resistant forms [31][32][33][34].…”
Section: Resultsmentioning
confidence: 99%
“…In line with these facts, berberine was chosen for the study to identify its potential targets in red complex pathogens. Our research team has embarked on identifying the potential molecular targets of different plant compounds against dental pathogens with a special emphasis on periodontal pathogens and emerging drug resistant species [22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, there is a need for a search of an alternate antidiabetic agent [19]. Evidence has shown that copper nanoparticles synthesised from medicinal plant Dioscorea bulbifera tuber extract showed antioxidant and antidiabetic activity [20].Our team has extensive knowledge and research experience that has translate into high quality publications [21][22][23][24][25][26][27][28][29][30][31][32], [33][34][35][36][37]. [38] [39] [40].…”
Section: Introductionmentioning
confidence: 99%